A primer in theory construction - Reynolds, Paul D. (Paul Davidson), 1938- (Boston : Pearson/AandB, 1971)
The book discusses scientific theories in general terms, but also addresses the special challenges of developing scientific knowledge about social and human phenomena.
Originally published: Indianapolis : Bobbs-Merrill, 1971.
"Complete text of the original copyright 1971 version, with new typography and page design"--P. 4 of cover.
Includes bibliographical references (p. 177-181) and indexes.
rua 02/12/13
Loans
Keywords: Social sciences